Moringa Oleifera Seed Protein Hydrolysates Inhibit Haemoglobin Glycosylation and #x3B1;-Glucosidase Activity in-Vitro (Global Journal of Medical Research, 2019)
In recent times, the biological activities of enzymatic digests of plant and animal proteins have been investigated and have been shown to exhibit multidirectional effects against key enzymes involved in the pathophysiology of a number of diseases. The present study evaluated the inhibitory effects of M.oleifera seed protein hydrolysates on haemoglobin glycosylation and #x3B1;-glucosidase. Proteins were hydrolyzed using the enzymes pepsin, trypsin, papain and chymotrypsin. The resulting hydrolysates were evaluated for inhibitory activities against non-enzymatic haemoglobin glycosylation as well as #x3B1;- glucosidase. Peptic and chymotrypsin hydrolysates demonstrated the best inhibitory effects against hemoglobin glycosylation, while chymotryptic and tryptic hydrolysates had better #x3B1;-glucosidase inhibitory activities. Kinetic data showed that the hydrolysates inhibited #x3B1;-glucosidase inhibitory effects by different mechanisms, such tryptic and chymotrypsin hydrolysates indicated a competitive mode of inhibition while papain and pepsin hydrolysates displayed mixed inhibition of #x3B1;-glucosidase. These results suggest that M.oleifera seed proteins contain peptides that can be harnessed to formulate peptides which could serve as novel alternatives to current therapies in the management of diabetes mellitus.
Keywords: Moleifera; hydrolysates; pepsin; trypsin; papain; chymotrypsin; hemoglobin; #x3B1; -glucosidase; diabetes mellitus